Profil Kompleksitas Soal Matematika Siswa Visualizer dan Verbalizer dalam Post Solution Problem-Posing - Anisha Wahyuni Novianti; Lisanul Uswah Sadieda; Suparto Suparto (JRPM (Jurnal Review Pembelajaran Matematika), 2020)
This research aimed to describe the question complexity of the visualizer and verbalizer students in problem posing. The question complexity on problem posing is the complexity of the questions made by students by paying attention to some aspects, which are language variable, question complexity level, and students' creativity thinking level. This is descriptive research with a qualitative approach. The subjects were two visualizer students and two verbalizer students from 11th grade of Al Falah Senior High School. Data collecting techniques are tests and interviews. Test and interview data were analyzed descriptively. In the final result, question complexity of the visualizer students tend on the language variable level is second (low), question complexity is easy, and the creative thinking level is third (creative). Whereas the verbalizer students tend on the language variable level is fourth (high), question complexity is high, and the creative thinking level is fourth (extremely creative).